Analysis Of Economic Efficiency On Applied Of Synchronization Technology In Dairy Cows At Small Farmers - Supardi Rusdiana; Umi Adiati; Diana Andrianita Kusumaningrum; Chalid Talib (The International Journal of Tropical Veterinary and Biomedical Research, 2020)
Abstract